The Risk of Mortality and the Factor V Leiden Mutation in a Population-based Cohort - Heijmans, Bastiaan T.; Westendorp, Rudi G. J.; Knook, Dick L.; Kluft, Cornelis; Slagboom, Eline P. (Thrombosis and Haemostasis, 1998)
The factor V Leiden mutation (conferring resistance to activated protein C) has been implicated in the risk of arterial thrombosis and is a well-established risk factor for venous thrombosis especially in the elderly. We studied whether the disease association of the factor V mutation is reflected in an increased all-cause and cause-specific mortality.First, the prevalence of the factor V Leiden mutation was determined in a population-based study among subjects aged 85 years and over (4.7%, n = 660) and was found to correspond to the prevalence in young subjects aged 18 to 40 years (5.0%, n = 321). Secondly, we studied the association of factor V Leiden with the risk of all-cause mortality and specific causes of death in the elderly cohort during a 10-year follow-up period. Neither the all-cause mortality risk (RR 1.0; 95% CI, 0.7-1.5), nor the risk of death due to cardiovascular disease (RR 0.9; 95% CI, 0.5-1.7) were increased in elderly subjects heterozygous for factor V Leiden. Our study thus indicates that heterozygosity for factor V Leiden does not affect population mortality.